Rozwiązane

(x-3)(5-x)-2=(2-x)(x-4)=3

(6-x)(x-2)+(x+3)(x-4)=2x+5

(2x-5)(x+1)-2=(1-x)(8-2x)+2x

-5x+12+x=2x-12

-3+2x-6=3-4x



Odpowiedź :

(x-3)(5-x)-2=(2-x)(x-4)+3
5x-x²-15+3x-2 = 2x-8-x²+4x+3 (x² zredukują się)
5x+3x-2x-4x = -9+3+15+2
2x = 11 /:2
x=5,5

(6-x)(x-2)+(x+3)(x-4)=2x+5
6x-12-x²+2x+x²-4x+3x-12=2x+5
6x+2x-4x-3x-2x=5+12
-x = 17 /:(-1)
x=-17

(2x-5)(x+1)-2=(1-x)(8-2x)+2x
2x²+2x-5x-5-2=8-2x-8x+2x²+2x
2x-5x+2x+8x-2x=8+5+2
5x=15 /:5
x=3

-5x+12+x=2x-12
-5x+x-2x=-12-12
-6x=-24 /:(-6)
x=4

-3+2x-6=3-4x
2x+4x=3+3+6
6x=12 /:6
x=2
(x-3)(5-x)-2=(2-x)(x-4)=3
to zadanie ma dwa znaki = i niewiem który jest właściwy, napisz gdzie ma być = to rozwiążę

(6-x)(x-2)+(x+3)(x-4)=2x+5
6x -12 -x² +2x+ x² -4x +3x -12 = 2x + 5
6x + 2x -4x +3x -2x = 5 +12 + 12
5x = 29 /:5
x = 5,8

(2x-5)(x+1)-2=(1-x)(8-2x)+2x
2x² + 2x - 5x - 5 -2=8 -2x -8x +2x² + 2x
2x - 5x +2x +8x -2x= 8 + 5 + 2
5x = 15 /:5
x = 3

-5x+12+x=2x-12
-5x + x - 2x =-12 - 12
-6x = -24 /:(-6)
x = 4

-3+2x-6=3-4x
2x + 4x = 3 + 3 + 6
6x = 12 /:6
x = 2

Inne Pytanie